A Multidrug-Resistant Escherichia coli Caused the Death of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Mingyang Xue; Xiaowei Hu; Nan Jiang; Wei Liu; Zidong Xiao; Chunjie Zhang; Yeying Wu; Tianwang Liang; Huixuan Zhang; Yuding Fan; Yan Meng; Yong Zhou (Veterinary Sciences)
The rapid increase in drug resistance in recent years has become a significant global public health concern. Escherichia coli are ubiquitous bacteria, widely distributed in various environments. This study isolated a bacterial strain (HD-593) from diseased Chinese soft-shelled turtles (Pelodiscus sinensis). The bacterium was identified based on morphology, biochemical tests, and 16S rRNA sequencing, confirming it as E. coli. Drug susceptibility tests revealed that the HD-593 strain was highly resistant to ceftriaxone, enrofloxacin, doxycycline, sulfadiazine, gentamicin, neomycin, florfenicol, carbenicillin, cefradine, erythromycin, penicillin, ampicillin, midecamycin, and streptomycin. Resistance gene analysis confirmed the presence of quinolone resistance genes (oqxA and oqxB), aminoglycoside resistance genes (aac(3)-II and aphA1), a β-lactam resistance gene (blaTEM), and an acylaminol resistance gene (floR) in HD-593. The median lethal dose (LD50) of HD-593 for P. sinensis was 6.53 × 105 CFU/g. Biochemical analysis of serum revealed that HD-593 infection caused a significant reduction in total protein, albumin, and globulin levels, while markedly increasing the levels of aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase. Histopathological analysis revealed severe intestinal damage characterized by villi detachment and muscle cell necrosis. Additionally, extensive splenocyte necrosis with nuclear marginalization, glomerular swelling, and pronounced hepatic steatosis accompanied by distended sinusoids were observed. This study identified a multidrug-resistant E. coli strain from deceased P. sinensis, suggesting that drug resistance genes may circulate in aquaculture ecosystems, posing potential risks to aquaculture.